Konsep Kelahiran Baru Dalam Pembelajaran Pendidikan Agama Kristen - Oci, Markus (Sekolah Tinggi Teologi Kanaan Nusantara, 2020)
Abstract. Christian Education as an educational process that is an essential effort by teachers or educators aimed at students in the learning process. The education contains teachings, Christian values, and emphasis on the three aspects, namely: cognitive (knowledge), affective (attitude), psychomotor (skills and skills), which in the process of teaching and learning activities knowledge about the Bible including dogmas that are based on the truth of God's Word (Biblical). The subjects of Christian Religious Education are churches and schools. The Object of Christian Religious Education is teaching and learning activities consisting of believers of all ages (from children to the elderly). This research uses the literature method. The New Birth is born again by God for every believer in the Lord Jesus Christ. As an implication of Christian Religious Education, one of them is about